The impact of rural resettlement on livelihoods : a case of Isara resettlement site in Dawuro, Ethiopia - Dubale, Tekalign Gunjefo (2010)
Resettlement as a response to food security has been practised in Ethiopia since the imperial regime. In all the respective governments, the aim was superficially the same-moving people from drought affected areas or over populated regions and over utilized land settlement to the so called fertile arable lands. Despite the different motives the programme has been launched, it has its own positive and negative impact on the relocated and the host community. Based on this background, this study explores the impact of the current Ethiopian resettlement on the livelihoods of the host and resettler community at Isara resettlement site of Dawuro Zone in Southern Nations, Nationalities and Peoples` Region (SNNPR) - a region which embraces over 56 ethnic groups. With the multi-cultural context of this region, the resettlement was carried out within the region from one zonal administration to the other zonal or special district administration. Accordingly, people from the Hadiya, Kambata, Tambaro, and Wolayta ethnic zones were moved to Dauwro ethnic zone. The people relocated from these zonal administrations have different socio-economic, cultural and historical backgrounds with the receiving zone, Dawuro Zone. According to the national rural development policy, resettlement was taken as a strategy to alleviate the plight of food security by moving people within the same region of similar socio-cultural, linguistic and historical make up. But the practice in SNNPR basically violates this reality and pushed to be implemented as a region. This study looks into the challenges of this context to maintain livelihood in the new area of settlement. It answers the following questions: what impacts does the resettlement have on the host and resettler community. What livelihood activities are practised by the resettler and host community? What is the current status of the livelihoods for the resettlers and host communities? The study clearly shows that the current resettlement practice at Isara site has predominantly negative impact on the livelihoods of the host and resettler communities. This impact was traced back to the poor provision of social and agricultural input services to the relocatees and the inconsistency of the promised infrastructural and social service institutions in the site. Above all, the inappropriate use or deforestation of the locally available livelihood resource made the matter worst. Meanwhile the growing number of relocated people in the new site aggravated the clearing of more forest land to agricultural settlement. This inevitably caused the ecological imbalance in the site. This contradicts with the basic livelihood concept which incorporates - the capacity, resources affordable and the activities to make a living. Here the demolished local forest and land resources cut of f the above livelihood cycle. Likewise, the capacity where the labour force is the dominant source, is affected by the poor psycho-social support for the relocated and challenge of social networking in the new site hinders the work force motivation and welfare. The poor health and education services in the site hold back the health status of the productive power and thus affect the capacity to make livelihood. Over all, the resettlement launched at Isara site has resulted in the loss of natural resources, and thus has dwindled the effort to sustain their livelihood for the present and future.